2020
DOI: 10.1080/10256016.2020.1810683
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and ammonium differ in their impact on δ13C of plant metabolites and respired CO2from tobacco leaves

Abstract: The carbon isotopic composition (δ 13 C) of foliage is often used as proxy for plant performance. However, the effect of NO3vs. NH4 + supply on δ 13 C of leaf metabolites and respired CO2 is largely unknown. We supplied tobacco plants with a gradient of NO3to NH4 + concentration ratios and determined gas exchange variables, concentrations and δ 13 C of TCA cycle intermediates, δ 13 C of dark respired CO2, and activities of key enzymes nitrate reductase, malic enzyme and phosphoenolpyruvate carboxylase.Net assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Our results of the N treatment experiment also provide evidence that the change in the relative abundance of plant compounds and its consequences for hydrogen isotope patterns in plants is strongly interlinked with various biophysical traits (Fig. 4), which function as indicators of plant performance and were deduced from a previous study performing the same experiment but focusing on carbon isotope fractionation (48). We found that tobacco plants having higher relative starch than sugar concentrations under high NO 3 − treatments performed well, as indicated by biomass production and A net being at the highest (Fig.…”
Section: Identifying Major Drivers Of δ 2 H Variations In Plant Compo...supporting
confidence: 73%
See 2 more Smart Citations
“…Our results of the N treatment experiment also provide evidence that the change in the relative abundance of plant compounds and its consequences for hydrogen isotope patterns in plants is strongly interlinked with various biophysical traits (Fig. 4), which function as indicators of plant performance and were deduced from a previous study performing the same experiment but focusing on carbon isotope fractionation (48). We found that tobacco plants having higher relative starch than sugar concentrations under high NO 3 − treatments performed well, as indicated by biomass production and A net being at the highest (Fig.…”
Section: Identifying Major Drivers Of δ 2 H Variations In Plant Compo...supporting
confidence: 73%
“…Both experiments are described to cause substantial changes in leaf gas exchange (e.g., assimilate rates and stomatal conductance) and assimilate pools (e.g., sugar and starch concentrations). In the first experiment (48), tobacco plants were treated with 6 mM N fertilization solutions differing in their nitrate to ammonium ratio (NO 3…”
Section: Biochemical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO 3 – -N is easily dissolved and has high activity in the soil, which can quickly provide nitrogen nutrition for crops; however, it is also easy to lose. This characteristic meets the growth demand for tobacco; tobacco grows rapidly and can turn senescence and mature at an appropriate time ( Ghiasi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…Elevated air temperatures, which result in higher surface soil temperatures, can accelerate soil microbial activity, promoting SOM decomposition and N mineralization, thus increasing needle N content. N is vital for photosynthesis, particularly for enzymes like Rubisco (Evans, 1989; Ghiasi et al., 2020). In the circum‐Arctic ecosystem, located above 67°N latitude, tree‐ring data suggest that tree growth responds positively to rising summer temperatures (Tei & Sugimoto, 2018).…”
Section: Discussionmentioning
confidence: 99%